ABORSI DALAM PERSPEKTIF HUKUM ISLAM - Nelly Yusra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
This paper describes the phenomenon of abortion that is currently so prevalent in society. This fact requires us to find solutions quickly and accurately, so that people do not walk toward ruin, caused by the strong influence of ideology adopted by the society of freedom blindly from the West. Islam as a religion is perfect and complete, is the main solution to problems in every line of human life, in this case remove followabortion that violates the rules of Islamic law, in addition to the consideration that Indonesia is a Muslim majority. This paper aims to find Islamic views on abortion and find the best solution according to Islam to combat the practice of abortion that are implicated in the middle of the “ummah”, which causes women to be the greatest sacrifice.